2011
DOI: 10.1177/0300985811427151
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Glomerular and Tubulointerstitial Lesions in Common Marmosets (Callithrix jacchus)

Abstract: Spontaneous progressive nephropathy dominated by glomerular lesions in common marmosets has been reported. However, the histopathologic characteristics, including the relationship between glomerular and tubulointerstitial lesions, have not been described in detail. In the present study, the authors examined the histopathologic characteristics of the background renal lesions in common marmosets (3 males and 9 females, 3 to 8 years old). The severity of glomerular lesions was graded into 3 classes: grade I, no a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 15 publications
(24 reference statements)
5
19
0
Order By: Relevance
“…Recently, a correlation between expansion of mesangial matrix and age and between glomerular and tubulointerstitial lesions was reported by Isobe et al (2012). They revealed that the increase in mesangial matrix progressed with age, and the tubulointerstitial lesions were correlated with the glomerular lesions.…”
Section: Introductionmentioning
confidence: 96%
“…Recently, a correlation between expansion of mesangial matrix and age and between glomerular and tubulointerstitial lesions was reported by Isobe et al (2012). They revealed that the increase in mesangial matrix progressed with age, and the tubulointerstitial lesions were correlated with the glomerular lesions.…”
Section: Introductionmentioning
confidence: 96%
“…Acute experimental liver damage in cirrhotic rats also induced renal dysfunction with increases in serum creatinine, bilirubin, and BUN levels [85]. Collectively, these data suggest that GBV-B, like many other viral infections, could induce kidney dysfunction, but it is also important to point out that marmosets have a propensity to develop spontaneous benign glomerulonephropathy [86–88]. Thus, further studies will be necessary to determine if kidney disease is a true complication of GBV-B infection.…”
Section: Discussionmentioning
confidence: 99%
“…Spontaneous progressive nephropathy dominated by glomerular lesions in common marmosets has been reported 20 , 21 . The historical renal lesion in common marmosets is characterized by glomerular lesions with an increase in mesangial matrix, which progresses with aging, and secondary tubulointerstitial lesions, including tubular hyperplasia 20 .…”
Section: Discussionmentioning
confidence: 99%
“…The historical renal lesion in common marmosets is characterized by glomerular lesions with an increase in mesangial matrix, which progresses with aging, and secondary tubulointerstitial lesions, including tubular hyperplasia 20 . In our study, two non-treated control animals showed remarkable tubulointerstitial nephritis without any glomerular changes and interstitial fibrosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation